Laparoscopic Versus Open Hemihepatectomy: The ORANGE II PLUS Multicenter Randomized Controlled Trial - Fichtinger, Robert S; Aldrighetti, Luca A; Abu Hilal, Mohammed; Troisi, Roberto I; Sutcliffe, Robert P; Besselink, Marc G; Aroori, Somaiah; Menon, Krishna V; Edwin, Bjørn; D'Hondt, Mathieu; Lucidi, Valerio; Ulmer, Tom F; et al. (Journal of clinical oncology, 2024)
To compare outcomes after laparoscopic versus open major liver resection (hemihepatectomy) mainly for primary or metastatic cancer. The primary outcome measure was time to functional recovery. Secondary outcomes included morbidity, quality of life (QoL), and for those with cancer, resection margin status and time to adjuvant systemic therapy. This was a multicenter, randomized controlled, patient-blinded, superiority trial on adult patients undergoing hemihepatectomy. Patients were recruited from 16 hospitals in Europe between November 2013 and December 2018. Of the 352 randomly assigned patients, 332 patients (94.3%) underwent surgery (laparoscopic, n = 166 and open, n = 166) and comprised the analysis population. The median time to functional recovery was 4 days (IQR, 3-5; range, 1-30) for laparoscopic hemihepatectomy versus 5 days (IQR, 4-6; range, 1-33) for open hemihepatectomy (difference, -17.5% [96% CI, -25.6 to -8.4]; < .001). There was no difference in major complications (laparoscopic 24/166 [14.5%] open 28/166 [16.9%]; odds ratio [OR], 0.84; = .58). Regarding QoL, both global health status (difference, 3.2 points; < .001) and body image (difference, 0.9 points; < .001) scored significantly higher in the laparoscopic group. For the 281 (84.6%) patients with cancer, R0 resection margin status was similar (laparoscopic 106 [77.9%] open 122 patients [84.1%], OR, 0.60; = .14) with a shorter time to adjuvant systemic therapy in the laparoscopic group (46.5 days 62.8 days, hazard ratio, 2.20; = .009). Among patients undergoing hemihepatectomy, the laparoscopic approach resulted in a shorter time to functional recovery compared with open surgery. In addition, it was associated with a better QoL, and in patients with cancer, a shorter time to adjuvant systemic therapy with no adverse impact on cancer outcomes observed.